"Old" and "New" Mass Killing? Genocide and Politicide Occurrence and Severity During and After the Cold War. Issue 4 (19th May 2022) - Hendrickson, Petra
ABSTRACT: How did the Cold War impact the occurrence and severity of genocide and politicide? The Cold War is known to have impacted a number of conflict dynamics, yet its influence on genocide and politicide, the most severe forms of state-driven anti-civilian violence, remains unexplored. This article argues that genocide and politicide have followed a number of worldwide trends, like increased democracy and the decreased frequency of intrastate conflict, which have had dampening effects on genocide and politicide. Probit and ordered probit analyses reveal that genocide and politicide occurrence was more frequent during the Cold War, but that the effect of the Cold War on severity depends on model specification; using 1992 as the first year of the post-Cold War era, genocides and politicides are more severe after the end of the Cold War.